Human Herpes Virus 8 in HIV-1 infected individuals receiving cancer chemotherapy and stem cell transplantation. - Louise E Hogan (PLoS ONE, 2018)
BACKGROUND:Human Herpes Virus 8 (HHV8) can cause Kaposi's Sarcoma (KS) in immunosuppressed individuals. However, little is known about the association between chemotherapy or hematopoietic stem cell transplantation (HSCT), circulating HHV8 DNA levels, and clinical KS in HIV-1-infected individuals with various malignancies. Therefore, we examined the associations between various malignancies, systemic cancer chemotherapy, T cell phenotypes, and circulating HHV8 DNA in 29 HIV-1-infected participants with concomitant KS or other cancer diagnoses. METHODS:We quantified HHV8 plasma viral loads and cell-associated HHV8 DNA and determined the relationship between circulating HHV8 DNA and lymphocyte counts, and markers of early and late lymphocyte activation, proliferation and exhaustion. RESULTS:There were no significant differences in plasma HHV8 DNA levels between baseline and post-chemotherapy time points or with the presence or absence of clinical KS. However, in two participants circulating HHV8 DNA increased following treatment for KS or HSCT for lymphoma,. We observed an approximately 2-log10 reduction in plasma HHV8 DNA in an individual with KS and multicentric Castleman disease following rituximab monotherapy. Although individuals with clinical KS had lower mean CD4+ T cell counts and percentages as expected, there were no significant associations with these factors and plasma HHV8 levels. We identified increased proportions of CD8+ and CD4+ T cells expressing CD69 (P = 0.01 & P = 0.04 respectively), and increased CD57 expression on CD4+ T cells (P = 0.003) in participants with detectable HHV8. CONCLUSION:These results suggest there is a complex relationship between circulating HHV8 DNA and tissue-based disease in HIV-1 and HHV8 co-infected individuals with various malignancies.